Protein expression differs between neural progenitor cells from the adult rat brain subventricular zone and olfactory bulb - Maurer, Martin H.; Feldmann, Robert Enrico; Bürgers, Heinrich; Kuschinsky, Wolfgang (BMC neuroscience, 2008)
Neural progenitor cells can be isolated from various regions of the adult mammalian brain, including the forebrain structures of the subventricular zone and the olfactory bulb. Currently it is unknown whether functional differences in these progenitor cell populations can already be found on the molecular level. Therefore, we compared protein expression profiles between progenitor cells isolated from the subventricular zone and the olfactory bulb using a proteomic approach based on two-dimensional gel electrophoresis and mass spectrometry. The subventricular zone and the olfactory bulb are connected by the Rostral Migratory Stream (RMS), in which glial fibrillary acidic protein (GFAP)-positive cells guide neuroblasts. Recent literature suggested that these GFAP-positive cells possess neurogenic potential themselves. In the current study, we therefore compared the cultured neurospheres for the fraction of GFAP-positive cells and their morphology of over a prolonged period of time.
Gesehen am 30.04.2021